Integrating process for agro-ecotourism marketing of Sam Ruean community, Thailand - KONGDIT, S.; RATANAPONGTRA, T. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT The objectives of this research are 1) to study the model and strategy of agro-ecotourism of the Sam Ruean community, 2) to study the integration process of special interest tourism marketing to create a niche market-based tourism network, and 3) to propose the integrating process of the agro-ecotourism marketing. The samples were community tourism stakeholders. The study results can be summarized as follows:  The integrating process of the agro-ecotourism marketing of the Sam Ruean community revealed that they have a tourism marketing model that could be linked to two specific marketing types. RESUMEN Los objetivos de esta investigación son 1) estudiar el modelo y la estrategia de agroecoturismo de la comunidad Sam Ruean 2) estudiar el proceso de integración del marketing turístico de interés especial para la creación de una red de turismo de nicho de mercado; y 3) proponer el proceso integrador de la comercialización del agroecoturismo. Las muestras fueron partes interesadas del turismo comunitario. Los resultados del estudio se pueden resumir de la siguiente manera: El proceso de integración del marketing de agroecoturismo de la comunidad de Sam Ruean reveló que la misma tiene un modelo de marketing turístico que podría vincularse a dos tipos de marketing específicos